Post-registration experience of nivolumab in advanced hepatocellular carcinoma: an international study - Dominik Bettinger; Bo Yu; David Szafron; Yinghong Wang; Mahvish Muzaffar; Thomas Marron; Uqba Khan; Yi-Hsiang Huang; David J Pinato; Ahmed Kaseb; Anwaar Saeed; Tomi Jun; et al. (Journal for ImmunoTherapy of Cancer)
Background Nivolumab is Food and Drug Administration approved in sorafenib-experienced, advanced hepatocellular carcinoma (HCC). Post-registration data of treatment in a real-world setting is lacking.Patients and methods We performed an international, multicenter observational study to confirm safety and efficacy of nivolumab in 233 patients treated outside clinical trials from eight centers in North America, Europe and Asia.Results Patients received nivolumab for Barcelona Clinic Liver Cancer stage C (n=191, 92.0%) and Child-Pugh (CP) A (n=158, 67.8%) or B (n=75, 32.2%) HCC as first (n=85, 36.5%) or second to fourth systemic therapy line (n=148, 63.5%). Objective response rate (ORR) was 22.4% and disease control rate was 52.1%. Median overall survival (OS) was 12.2 months (95% CI 8.4 to 16.0) and median progression-free survival was 10.1 months (95% CI 6.1 to 14.2). Treatment-related adverse events of grade >2 occurred in 26 patients (11.2%). Efficacy and safety were similar across CP classes and therapy line. OS was shorter in CP-B than A (7.3 months vs 16.3 months, p<0.001) and in post-first line use (10.4 months vs 16.3 months, p=0.05). Achievement of an objective response predicted for improved OS (25.4 months vs 13.2 months, p<0.001).Conclusions This study confirms safety and efficacy of nivolumab in advanced HCC across various lines of therapy and degrees of liver dysfunction. Despite equal ORR and toxicity to nivolumab, patients with CP-B functional class have shorter survival than the patients with CP-A.